Causation, lawhood and determinism in electoral systems research: why 'Duverger's law' deserves to be called a law. Issue 1 (April 2018) - Weber, Erik; De Bal, Inge
Abstract In the 1950s, Maurice Duverger formulated several propositions connecting electoral systems and the number of political parties partaking in the election. For example, he put forward that a simple-majority single-ballot system favours the two-party system. This claim has been referred to asDuverger's law . Throughout the years, there has been a lot of debate about whether this claim (and other generalisations in the social sciences) deserves to be called a 'law'. In this paper, we defend the view that Duverger's law does deserve to be called a law. To argue for this, we present an account of lawhood based on the work of the philosopher Sandra Mitchell. In this account, the criterion for lawhood is spatio-temporal stability (and not, for example, determinism). We argue that spatio-temporal stability is the reason that many of the laws of physics are considered laws. We then show that Duverger's law is spatio-temporal in the same way that many of the laws of physics are. Correspondingly, we conclude that Duverger's law deserves to be called a law, as much as many of the laws of physics deserve this title. We finish with a reflection on the difference between determinism and lawhood, and argue that they should be separated conceptually.